Homes and Hands United: Bridging Housing and Labour Struggles at McMaster University - Elliot Goodell Ugalde (Radical Housing Journal)
[⚠️ Suspicious Content] "This paper examines the strategic alliance between the Tenant Solidarity Working Group (TSWG)—a graduate-student tenant union—and CUPE Local 3906, representing Teaching Assistants (TAs) and Research Assistants (RAs) at McMaster University in Hamilton, Ontario. Situated within Hamilton’s ongoing economic shift from manufacturing, specifically steel production, toward increased real estate speculation, financialization, and intellectual labour, this study investigates whether tenant-labour collaborations provide an effective model for addressing systemic socio-economic inequalities in student housing. Utilizing Nancy Fraser’s analytical triad of recognition, redistribution, and representation, the research evaluates the potential and limitations of this collaboration in achieving tangible socio-economic justice outcomes for graduate tenants. Through the lens of Fraser’s framework, the study identifies how tenant and labour activists mobilize recognition by contesting normative stigmatization of graduate renters; pursue redistribution through collective action that has yielded financial concessions such as rent reductions; and seek representation by demanding political inclusion within university administrative structures and broader public discourse. The analysis underscores that, despite Hamilton’s persistent identity as a major steel producer, the city's gradual pivot toward real estate investment and intellectual labour exemplifies David Harvey's concept of a ""spatial fix,"" redirecting surplus capital and labour into the university sector, thus complicating the intersection of housing affordability and labour precarity."